Failure of Heat Exchanger Return Bend Due to Long-Term Localized Overheating [Kerusakan pada Pipa Belokan U Alat Penukar Kalor akibat Panas Berlebih secara Lokal dalam Jangka Panjang] - Dewa Nyoman Adnyana (National Research and Innovation Agency (BRIN), 2019)
A return bend of a heat exchanger had failed due to bursting after it had been only about 2.5 years in service. The heat exchanger was used to transfer heat from hot combustion gas on the shell side to the feedstock oil on the tube side. Type and factors that may have caused the return bend bursting are discussed in this paper. The metallurgical assessment was conducted by preparing a number of specimens from the as-received burst and unburst return bends. Various laboratory examinations were performed including visual and macroscopic examination, chemical analysis, metallographic examination, hardness testing, and scanning electron microscopy equipped with energy-dispersive spectroscopy analysis. Results of the metallurgical assessment obtained showed that the burst return bend had been experiencing fracture overload due to local hot spot or long-term localized overheating occurred on the outer bend external surface. The long-term localized overheating was most likely caused by formation of fouling deposit that was built up on the outer bend internal surface, leading to increase the corrosion rate significantly and resulted in excessive metal loss or thinning occurred on the outer bend external surface. Consequently, the hoop stress at the outer bend section had been increasing significantly and eventually the working pressure of the feedstock oil on the tube side could burst the return bend wall thereonAbstrakTulisan ini menyajikan penelitian yang dilakukan pada sebuah belokan pipa U (return bend) pada sebuah alat penukar kalor yang mengalami kerusakan (pecah) setelah beroperasi hanya dalam waktu 2,5 tahun. Alat penukar kalor tersebut digunakan untuk memindahkan panas dari gas panas hasil pembakaran pada sisi bejana/tabung ke dalam bahan baku minyak (feedstock oil) pada sisi pipa. Material belokan pipa U tersebut dibuat dari baja karbon dengan standar ASTM A-234 Gr.WPB, memiliki diameter 2 inch dan tebal SCH 80. Penelitian berupa observasi dan pengujian metalurgi dilaksanakan dengan menyiapkan sejumlah sampel material dari belokan pipa U, baik yang sudah pecah maupun yang tidak pecah. Pengujian yang dilakukan meliputi uji visual dan makro, analisa kimia, uji metalografi, uji kekerasan dengan metoda Vickers dan SEM (scanning electron microscopy) - EDS (energy dispersive spectroscopy). Hasil pengujian metalurgi menunjukkan bahwa pipa belokan U yang pecah mengalami kerusakan akibat beban berlebih yang dipengaruhi oleh local hot spot atau panas berlebih secara lokal dalam jangka panjang (long-term localized overheating). Akibatnya, tegangan yang bekerja pada dinding belokan pipa U mengalami peningkatan yang sangat signifikan sehingga pada akhirnya tekanan operasi yang terjadi pada bahan baku minyak di dalam pipa dapat merobek atau memecahkan bagian dinding belokan pipa U tersebut.